Creating a Health Data Marketplace for the Digital Health Era - Imtiaz Khan, PhD; Mohamed A. Maher; Moderator: Anjum Khurshid, PhD (Blockchain in Healthcare Today)
With the advent of the General Data Protection Regulation (GDPR) of the EU and the development of technologies like blockchain and distributed ledger technologies (DLT), it is now possible to create a new paradigm with a shared economic model where financial Incentivization will be the main driver for data sharing. This can be achieved by setting up a digital health data marketplace (DHDM).